Designing Web-Based Exposure Triangle Simulation for Audio and Video Processing Techniques Course at Vocational High School with a Constructivist Approach - Budiyanto, Cucuk Wawan; Luthfi, Muhammad Zain Nur; Aristyagama, Yusfia Hafid (Journal of Vocational Education Studies, 2024)
This research is motivated by the need for adequate instructional tools and learning media in photography course at Vocational High School in Surakarta. The objectives of this research are to (1) design learning media with a constructivist approach for the exposure triangle learning material and (2) produce a learning media design that aligns with the needs of teachers and students. The research utilizes the Research and Development (R&D) method with a prototype development model involving six stages: communication, quick plan, modeling quick design, construction of prototype, and deployment delivery & feedback. Data were collected through interviews to determine the needs for media design, and the results were used to design learning media for the subject of Audio and Video Processing Techniques. The design was subsequently validated by subject matter experts and media experts before being tested on 31 Multimedia students in grade 12 at Vocational High School. The testing results indicated positive percentages from subject matter experts (82%) and media experts (85%), with an average System Usability Scale (SUS) score of 75.73. This suggests that the learning media is suitable for use and well-received by users. The media addresses practical challenges, such as limited access to DSLR cameras, and provides interactive simulations to bridge theoretical understanding and practical application.